Comparison of Barium and Arsenic Concentrations in Well Drinking Water and in Human Body Samples and a Novel Remediation System for These Elements in Well Drinking Water - Kato, Masashi; Kumasaka, Mayuko Y.; Ohnuma, Shoko; Furuta, Akio; Kato, Yoko; Shekhar, Hossain U.; Kojima, Michiyo; Koike, Yasuko; Dinh Thang, Nguyen; Ohgami, Nobutaka; Ly, Thuy Bich; Jia, Xiaofang; et al. (PLOS ONE, 2013)
Health risk for well drinking water is a worldwide problem. Our recent studies showed increased toxicity by exposure to barium alone (≤700 µg/L) and coexposure to barium (137 µg/L) and arsenic (225 µg/L). The present edition of WHO health-based guidelines for drinking water revised in 2011 has maintained the values of arsenic (10 µg/L) and barium (700 µg/L), but not elements such as manganese, iron and zinc. Nevertheless, there have been very few studies on barium in drinking water and human samples. This study showed significant correlations between levels of arsenic and barium, but not its homologous elements (magnesium, calcium and strontium), in urine, toenail and hair samples obtained from residents of Jessore, Bangladesh. Significant correlation between levels of arsenic and barium in well drinking water and levels in human urine, toenail and hair samples were also observed. Based on these results, a high-performance and low-cost adsorbent composed of a hydrotalcite-like compound for barium and arsenic was developed. The adsorbent reduced levels of barium and arsenic from well water in Bangladesh and Vietnam to <7 µg/L within 1 min. Thus, we have showed levels of arsenic and barium in humans and propose a novel remediation system.